A study of government regulation’s strategy for solving the algorithmic black-box puzzle of digital platforms: a complex network-based perspective - Zhu, Gehui; Tang, Mingliang; Jian, Xiao; Mu, Tong (Frontiers in Physics, 2025)
With the iteration of information technology and the enhancement of the arithmetic power of huge amounts of data, the economic model of digital platforms driven by data has become an important carrier of digital trade and digital economic development. By the reason of the dynamism, cross-border and complexity characteristics compared with traditional physical platforms, the development of digital platforms is no longer limited to the level of specific commodity goods or services, and the traditional regulatory system cannot match and adapt to the new attributes of digital platforms them. Therefore, the construction of a flexible, diversified and pluralistic co-management hybrid regulatory model is imminent. This article constructs small-world model to study government regulation of digital platforms. The small world model can effectively describe the connectivity between nodes (users, platforms, regulators, etc.) in the ecosystem of digital platforms, which helps researchers to understand the complexity of the network structure and the propagation pattern of information in the network and design more effective regulatory strategies. In addition, small-world models can be used to assess the robustness of regulatory measures in different scenarios, and to study the stability and information flow capability of the network in the face of node failure or attacks, reflecting the interaction between users and platforms. The research results and relevant discussion are as follows: First, the simulation results of government regulatory intensity indicate the government’s regulatory strength for the algorithmic black-box problem needs to be kept at an appropriate standard. Second, the simulation results government punishment intensity show that we can not only rely on a single regulatory means, but also need to take the composite strategy as far as possible, encouraging multiple bodies to participate in the regulation and collaborative governance to construct a fair and efficient digital transaction environment. Finally, the dynamic simulation results of sample size variation suggest that the government needs to adopt a variety of means to cooperate in forming an efficient and reasonable regulatory system to regulate digital platforms in accordance with the law, avoiding one-size-fits-all regulatory strategies.